Aristotle on Method and Metaphysics
X, 302 p.
Keywords: Aristotle on Method and Metaphysics is a collection of new and cutting-edge essays by prominent Aristotle scholars and Aristotelian philosophers on themes in ontology, causation, modality, essentialism, the metaphysics of life, natural theology, and scientific and philosophical methodology.